Fluid balance, diuretic use, and mortality in acute kidney injury - Grams, Morgan E; Estrella, Michelle M; Coresh, Josef; Brower, Roy G; Liu, Kathleen D (Clinical journal of the American Society of Nephrology, 2011)
Management of volume status in patients with acute kidney injury (AKI) is complex, and the role of diuretics is controversial. The primary objective was to elucidate the association between fluid balance, diuretic use, and short-term mortality after AKI in critically ill patients. Using data from the Fluid and Catheter Treatment Trial (FACTT), a multicenter, randomized controlled trial evaluating a conservative versus liberal fluid-management strategy in 1000 patients with acute lung injury (ALI), we evaluated the association of post-renal injury fluid balance and diuretic use with 60-day mortality in patients who developed AKI, as defined by the AKI Network criteria. 306 patients developed AKI in the first 2 study days and were included in our analysis. There were 137 in the fluid-liberal arm and 169 in the fluid-conservative arm (P=0.04). Baseline characteristics were similar between groups. Post-AKI fluid balance was significantly associated with mortality in both crude and adjusted analysis. Higher post-AKI furosemide doses had a protective effect on mortality but no significant effect after adjustment for post-AKI fluid balance. There was no threshold dose of furosemide above which mortality increased. A positive fluid balance after AKI was strongly associated with mortality. Post-AKI diuretic therapy was associated with 60-day patient survival in FACTT patients with ALI; this effect may be mediated by fluid balance.